HUBUNGAN POLA ASUH ORANG TUA DENGAN PERILAKU MENYIKAT GIGI PAGI HARI SETELAH SARAPAN DAN MALAM HARI SEBELUM TIDUR PADA ANAK PRASEKOLAH DI TK ATTAQWA MAJALAYA - Fajziah, Mau'lina; Laela, Dewi Sodja; Fatikhah, Nurul; Supriyanto, Irwan (Jurnal Terapi Gigi dan Mulut, 2024)
The Daily tooth brushing behavior in Indonesia reached 94.7% but only 2.8% did itcorrectly. By age group, only 1.1% of children aged 3-4 years brushed their teethcorrectly. The role of parents is very important in providing good parenting to trainchildren's motor skills. This study aimed to determine the relationship between parentingpatterns and tooth brushing behavior in the morning after breakfast and at night beforebedtime in preschool children at At-taqwa Majalaya Kindergarten. Analytic research witha cross-sectional approach. Samples were taken using random sampling techniquesdetermined using the Slovin formula, resulting in 47 respondents. The variables of thisstudy include parenting patterns in maintaining dental health measured using a parentingquestionnaire, knowledge and a checklist sheet of children's tooth brushing behavior.The results of the research analysis showed that the parenting category was good andthe category of children's tooth brushing behavior was correct. The research hypothesistested using the Chi-square test showed a p value = 0.001 (p <0.05) there was asignificant relationship. The relationship between parenting patterns is proven to affectthe accuracy of preschool children's tooth brushing behavior. With the application ofgood parenting from parents, children can get used to brushing their teeth at the righttime and effectively thereby increasing the degree of oral health.